2023
DOI: 10.21203/rs.3.rs-2665573/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holistic Bursting Cells Store Long-term Memory in Auditory Cortex

Abstract: The sensory neocortex has been since long suggested to be a substrate for long-term memory storage, yet which exact cells store long-term memories remained neither known nor visible over a century. Here, using a combination of day-by-day two-photon Ca2+ imaging and targeted single-cell loose-patch recording in a non-fear auditory associative learning paradigm, we reveal sparsely distributed neurons in layer 2/3 of auditory cortex emerged step-wise from quiescence into bursting mode, which then invariably expre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In rodents, it has also been shown that knowledge of the timing of auditory stimuli can also improve the speed of motor responses (Jaramillo & Zador, 2011) and that plasticity may be driven by changes in neuronal representation as early as primary sensory cortex (Chapuis & Chadderton, 2018;Huang et al, 2023;Knudstrup et al, 2024;J. Li et al, 2017;R. Li et al, 2023;.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, it has also been shown that knowledge of the timing of auditory stimuli can also improve the speed of motor responses (Jaramillo & Zador, 2011) and that plasticity may be driven by changes in neuronal representation as early as primary sensory cortex (Chapuis & Chadderton, 2018;Huang et al, 2023;Knudstrup et al, 2024;J. Li et al, 2017;R. Li et al, 2023;.…”
Section: Introductionmentioning
confidence: 99%